GROWTH AND EARLY REPRODUCTION DEVELOPMENT OF THE FIRST GENERATION OF SHEATFISH, Ompok miostoma (Vaillant, 1902) REARED IN CONTROLLED CONCRETE TANKS - Rudhy Gustiano; Vitas Atmadi Prakoso; Kurniawan Kurniawan; Wahyulia Cahyanti (Indonesian Aquaculture Journal, 2021)
This study was conducted to observe the growth and reproductive biology of wild sheatfish in controlled concrete tanks. The research was carried out from January to November 2020 at the Research Station for Freshwater Fisheries Germplasm, Cijeruk, Bogor. Sampled fish were captured from Cilala Lake in Bogor and Cipanas River in Sumedang, West Java. The collected fish were 14.6 ± 2.24 cm in length and 21.5 ± 9.19 g in weight. Growth and reproductive biology parameters were measured every 30 days. Cortisol, estradiol, vitellogenin, testosterone, glucose, and hemoglobin were also determined as the supporting parameters for gonadal maturity. Measured water quality parameters were temperature, pH, dissolved oxygen, ammonia, and alkalinity. The results showed that sheatfish grew with a specific growth rate of 0.4 ± 0.15%/day, FCR of 3.2 ± 0.26, and survival rate of 100%. Observation on the gonad maturity found that the fish studied were in the level-I and II. There are no significant differences regarding the supporting parameters (P>0.05) on the fish examined, despite the tendency of decreasing cortisol, and increasing testosterone. Based on the results, this study concludes that the observed fish can adapt, grow, and start to mature their gonads in their new environment, with temperature as one of the possible key factors influencing its gonad development.